Villages which have town’s origin– urbanistic and landscape values - Gawryluk, Dorota (Budownictwo i Architektura / Civil and Architectural Engineering, 2010)
There are places called: Andrzejewo, Radziłów, Wąsosz, Wizna in north-east Poland. They have parallel history since medieval age, when small towns were located, in 1870 they lost rights of town and they are villages till today. You can see historical structure of small town from 18th and 19th century of north-east Poland here in Andrzejewo, Radziłów, Wąsosz and Wizna.